Self-focusing: Past and Present Fundamentals and Prospects - Boyd, Robert W.; Lukishova, Svetlana G.; Shen, Y. R. (Topics in Applied Physics, 2009)
Self-focusing: Past and Present presents a comprehensive treatment of self-focusing and reviews both theoretical and experimental investigations of self-focusing. It connects the extensive early literature on self-focusing, filamentation, self-trapping, and collapse with more recent studies aimed at issues such as self-focusing of femtosecond pulses, white light generation, and the generation of filaments in air with lengths of more than 10 km. It also describes some modern advances in self-focusing theory including the influence of beam nonparaxiality on self-focusing collapse. In addition, this text reprints three key articles in the field, as well as the paper that describes the first laboratory observation of self-focusing phenomena with photographic evidence. Self-focusing: Past and Present is of interest to scientists and engineers working with lasers and their applications, as well as students, researchers, and laser and eye surgeons.